Hepatic resection prolongs overall survival in the selected patients with nasopharyngeal carcinoma liver metastases. Issue 10 (October 2022) - Feng, Yun; Zhao, Yi-Ming; Li, Wei-Wei; He, Xi-Gan; Zhou, Chang-Ming; Pan, Qi; Mao, An-Rong; Zhu, Wei-Ping; Hu, Chao-Su; Wang, Lu
Abstract: Background: The role of surgery in nasopharyngeal carcinoma liver metastases (NCLM) remains elusive, and the current application is limited. We aim to investigate whether hepatic resection (HR) of NCLM improves survival compared with non-hepatic resection (NHR) treatment. Methods: One hundred and thirty-three patients with NCLM from 2007 to 2017 were divided into two groups. Propensity score matching (PSM) analysis was used to compare the clinical outcomes. Results: After PSM the median overall survival (OS) and the 1, 3 and 5-year OS rates in HR group were 32.60 months, 86.2%, 37.3% and 37.3%, respectively; while for NHR group these values were 19.57 months, 61.5%, 12.9% and 2.9%, respectively (P = 0.008). Multivariate analysis indicated hepatitis B virus infection (P = 0.029) and hepatic resection (P = 0.018) were independent prognostic factors. Conclusion: Our study revealed that hepatectomy yields a survival benefit safely compared with systemic treatments, especially for patients with the size of largest metastasis < 5 cm, unilobar distribution of liver tumor and received unanatomical hepatectomy.